Doctor Retention in Ireland - Where Are the Failings That Prolong the Problem?; Comment on "Doctor Retention: A Cross-sectional Study of How Ireland Has Been Losing the Battle" - Gozie Offiah; Frank Murray; Consilia Walsh (Kerman University of Medical Sciences, 2021)
The issue of doctor retention has been a challenge in Ireland for many years. Poor working conditions including poor supervision, cost of training, bullying, worsening mentoring experiences and speciality specific issues are a substantial challenge faced by doctors in Ireland, thus leading to a higher degree of emigration. While some changes have been introduced to the system and have some positive effects, the root causes of doctor emigration have not been addressed. This commentary reviews the publication by Brugha et al published in the IJHPM in April 2020 on "Doctor Retention: A Cross-sectional Study of How Ireland Has Been Losing the Battle" and explains why the current system needs to change for the benefit of patient safety, doctor well-being and better patient care. Ireland's Health Service Executive intends to take steps towards developing a new model of medical workforce to address the issue of recruitment and retention challenges within the healthcare system.